Lymphomatoid papulosis: a clinical and histopathologic review and follow-up study of 34 cases in Taiwan - Jheng-Wei Lin; Wen-Jin Shiau; Ching-I. Lu; Chang-You Tsai; Wen-Ron Wong; Rosaline Chung-Yee Hui (Wolters Kluwer Medknow Publications, 2011)
Background: Lymphomatoid papulosis (LyP) is a rare condition within the spectrum of CD30+ cutaneous lymphoproliferative disorders that is not well documented in Taiwan. This study aimed to analyze its clinical manifestations, diagnostic histopathology, clinical course, and treatment response among Taiwanese. Methods: A retrospective chart review was performed on patients diagnosed with LyP at a Taiwanese medical center from 1992 to 2008. Results: There were 34 patients with biopsy-proven LyP. The mean age at diagnosis was 36 years (range: 10-75 years), with male predominance (male:female ratio 3:2). Type-A LyP was identified in 32 patients and Type C in 2 patients. Seven cases showed CD4 predominance and six cases showed CD8 predominance. Of the 34 LyP patients, 2 had coexistent non-Hodgkin's lymphoma, 1 (3%, 1/34) diagnosed before LyP onset and 1 (3%, 1/34) developed lymphoma 3 years after LyP. All of the patients were alive after a mean of 5.2 years (range: 3-12.7 years) of follow-up. Conclusions: Most of our cases are Type A LyP. No clinical features or pathologic features can predict increased risk for developing malignancy. Although only 6% (2/34) of LyP patients were found to have lymphoma in 3-year follow-up, longer follow up is needed. Regardless of treatment modalities, two-thirds of the patients have a recurrent and relapsing course. Observation is a reasonable approach for patients without cosmetic or symptomatic concerns.